USULAN PERBAIKAN WAREHOUSE FULFILLMENT PT XYZ TERHADAP EFISIENSI JARAK DAN BIAYA MATERIAL HANDLING DENGAN METODE SYSTEMATIC LAYOUT PLANNING (SLP) DAN ALGORITMA COMPUTERIZED RELATIVE ALLOCATION OF FACILITIES TECHNIQUE (CRAFT) - Ahmad Haris Setiawan, (2023)
In warehouse activities, such as searching, retrieving, preparing, and delivering goods (order picking), the warehouse layout is crucial to support the smooth flow of these processes. PT. XYZ, operating as a logistics aggregator and warehouse rental service provider, faces challenges related to the positioning of certain frequently accessed areas that are quite distant, hindering mobility, and potentially impeding the movement of material handling. Therefore, a reevaluation of the facility layout is conducted using the Systematic Layout Planning (SLP) method and the CRAFT algorithm. Analysis and calculations using the SLP method and CRAFT algorithm result in the smallest rectilinear distance of 5050.4 m/day, representing an efficiency improvement of approximately 22% from the initial rectilinear distance. Furthermore, there is a reduction in material handling costs by Rp 2,149,910/day with an efficiency rate of 24% from the previous material handling costs. The implementation of the proposed layout is expected to enhance efficiency and address operational challenges at PT XYZ's warehouse.